Preservation of juvenile hake (Merluccius merluccius L) in the western Mediterranean demersal trawl fishery by using sorting grids - Sardà, Francesc; Molí, Balbina; Palomera, Isabel (Scientia Marina, 2004)
The Mediterranean fishery has experienced a decline in catches over the past 20 years due to an excessive increase in effort caused by both increased trawler engine power and rapid technological advances in fishing technology and fish location. This has led to overexploitation, in which immature individuals support an increasing portion of the catches. The present study was undertaken to test a sorting grid and square-mesh-panel as juvenile exclusion systems. Our experience was a pilot study of such a system in the western Mediterranean. The purpose of these exclusion systems was to help juvenile hake escape from the net. The results demonstrate that the use of sorting grids for small fish in trawl gears in the Mediterranean is an efficient and practical means of avoiding the capture and discarding of unwanted individuals, with escape rates of over 50% (ranging between 50 and 90%). The grids were efficient and useful for excluding hake (Merluccius merluccius) on bottoms located at depths between 50 and 300 m, where hake are found all year round. A bar spacing of 20 mm yielded escape rates of L50 at 18.8 cm TL (L25 = 16.8 cm and L75 = 20.9 cm). Panels made of square meshes achieved poorer results than the grids. The grid system was effective for most of the species caught in the study area.